ETHNOARCHAEOLOGY AS A METHOD OF RECONSTRUCTING HUMAN LIFESTYLE (ON THE EXAMPLE OF FUNERARY RITUALS) (Scientific journal of the Fergana State University, 2026)
This article explores the theoretical and methodological foundations of ethnoarchaeology, its role in archaeological research, and its significance in reconstructing the human way of life. Furthermore, the study considers ethnoarchaeology as a scientific method aimed at reconstructing the material and spiritual culture of ancient societies. Using burial rituals as an example, the connection between archaeological data and ethnographic observations is analyzed, which makes it possible to gain a deeper understanding of the worldview, rituals, and social structure of ancient humans.